Integrating Multiple Aspects of Human-Elephant Conflict Management in Dharamjaigarh Forest Division of Chhattisgarh, India - Kumar, Aman; Dhuria, S. S.; Bhattacharya, Anindita; Sarkar, Prabal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Reducing human-elephant conflict (HEC) has recently been recognized as one of the important aspects of wildlife conservation worldwide. Hence, a site-specific study of the efficacy of different traditional methods is necessary to mitigate the HEC in a particular area. Data on elephant visits and the efficacy of different deterrent methods were collected from twelve forest villages in Dharamjaigarh Forest Division of Chhattisgarh, India through field surveys during 2017-21. Findings revealed that both the small male and family herds of elephants mostly visit during the evening hours (50.4%). Interestingly, the family herd of the elephants preferred (95%) the agricultural plot while the small male herd visited mostly (80%) the village area during the entire study period. Making noise was the most common (100%) method practiced by all the villages followed by a fireball (80%). However, in 20% of the cases observed, noise, fireballs, and firecrackers were used to chase out elephants. There were variations in success rate attempts where a maximum (41.7%) was observed in Kudelela and a minimum in Potia (26.4%). Hence, the traditional method is found to be efficient in mitigating the HEC to some extent, however, modern technologies need to be integrated for accruing more efficient results.